PENGARUH PEMBERIAN JUS BUAH NAGA MERAH TERHADAP TEKANAN DARAH PADA PRA-LANSIA PENDERITA HIPERTENSI DI WILAYAH DESA CIPANAS RT.04/RW.01 KECAMATAN CIPANAS KABUPATEN CIANJUR TAHUN 2025 - Putri Nurhalimatussa’diyah; Indri Sarwili; Rina Afrina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Hypertension is a non-communicable disease with a steadily increasing prevalence, especially in the pre-elderly. In addition to pharmacological therapy, hypertension can be controlled through non-pharmacological therapies based on natural ingredients, one of which is red dragon fruit juice (Hylocereus polyrhizus). This study aims to determine the effect of red dragon fruit juice on blood pressure in pre-elderly hypertensive patients in Cipanas Village, RT 04/RW 01, Cipanas District, Cianjur Regency, in 2025. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 respondents selected using a purposive sampling technique. The intervention consisted of red dragon fruit juice made from 100 grams of fresh red dragon fruit flesh without added sugar, administered for three consecutive days. Blood pressure measurements were taken before and after the intervention using a sphygmomanometer. Data were analyzed using univariate and bivariate analysis with the Wilcoxon Signed Rank Test. The results showed that the average systolic blood pressure decreased from 152.17 mmHg to 126.33 mmHg, and the diastolic blood pressure decreased from 93.50 mmHg to 72.50 mmHg. Statistical tests showed a significant effect of red dragon fruit juice on reducing systolic and diastolic blood pressure, with a p-value of 0.000 (p < 0.05). The conclusion of this study is that red dragon fruit juice significantly reduces blood pressure in pre-elderly individuals with hypertension.